Development of MS ISO/IEC 17025 quality system (general requirements for the competence of testing and calibration laboratories) for FKM laboratory - Lew, Hon Chung (2009)
This report describe about the development of MS ISO/IEC 17025:2005 quality manual and system procedure for FKM laboratory, University Malaysia Pahang (UMP). This report consists of five chapters which are Introduction, Literature Review, Methodology, Results and Conclusion. The objectives of this project are study and identify the clauses of MS ISO/IEC 17025:2005 and develop the quality manual and system procedure according to the standard requirement for FKM laboratory. Studies and understanding the clauses is important before developing the quality manual and system procedure. This standard is divided to two main requirements which are management requirement and technical requirement. The management requirement of this standard is similar with the requirement of ISO 9001. The requirement of ISO 9001 was being studies. A workshop of MS ISO/IEC 17025:2005 was being attended to understand more clear on the clauses and some important information to develop the quality manual and system procedure. After that, one of the accredited MS ISO/IEC 17025 laboratories has been chosen to visit. It was also to understand more deep in developing the quality manual and system procedure; and ensures that the quality manual and system procedure is developing in the right path. The quality manual is developing as the policy and objective of the laboratory. The system procedure will been develop as a procedure to achieve the objective of the quality manual. The forms are creating as an evidence to support the requirements of the standard. The quality manual had been developed from clause 4.9 to clause 4.15 which is clauses of management requirement of the standard. The system procedure also had been developed for each of the clauses except the clause 4.10 improvement. This clause not required any system procedure because this clause had related with the entire clause to ensure that the quality management system is continual improve. Some of the form had been created such as Non-Conforming Investigation Form, Corrective and Preventive Action Form. The schedule for the internal audit and management review had been developed. The audit checklist had been created for the auditor use during the audit process. All the documents will be proposed to FKM laboratory for the accreditation of MS ISO/IEC 17025:2005. In conclusion, the objective of the project had been achieved where the entire related document had been developed.